Human papillomavirus-related esophageal cancer survival: A systematic review and meta-analysis. Issue 46 (November 2016) - Guo, Lanwei; Liu, Shuzheng; Zhang, Shaokai; Chen, Qiong; Zhang, Meng; Quan, Peiliang; Sun, Xi-Bin
Abstract: Background: Human papillomavirus (HPV) has been identified to be related to progression of esophageal cancer. However, the results remain controversial. A meta-analysis of epidemiologic studies was therefore conducted to address this issue. Methods: The electronic databases of MEDLINE and Excerpta Medica database were searched till April 30, 2016. Study-specific risk estimates were pooled using a random-effects model. Results: Ten studies involving a total of 1184 esophageal cancer cases were included in this meta-analysis. The pooled hazard ratio comparing HPV-positive to HPV-negative esophageal cancers was 1.03 (95% confidence interval 0.78–1.37), which was not significantly correlated with improved survival. However, HPV-16-positive patients might have a significantly favorable survival (hazard ratio 0.73, 95% confidence interval 0.44–1.21). Conclusion: The meta-analysis indicated that HPV infection may not be of prognostic utility in the evaluation of factors contributing to esophageal cancer. Further large prospective studies are encouraged to stratify survival analysis by HPV type. Abstract : Supplemental Digital Content is available in the text